المعالجة الإعلامية لتدعيات حضور الرئيس الصحراوي لقمة تيكاد اليابان إفريقيا على العلاقات التونسية المغربية - محبوبي إبراهيم; محمد صالح الولي; د/علال عبد القادر (جامعة عمار ثليجي الاغواط, 2023)
ملخص دراسة: تناولت هذه الدراسة موضوع المعالجة الإعلامية لتداعيات حضور الرئيس الصحراوي في قمة تيكاد على العلاقات التونسية المغربية، نظرا لدور الهام الذي تلعبه البرامج التلفزيونية في المعالجة الإعلامية للقضايا السياسية ركزنا في دراستنا حول المعالجة الإعلامية لتداعيات حضور الرئيس الصحراوي في قمة تيكاد على العلاقات التونسية المغربية في قناة دف الكشف عن طبيعة المعالجة الإعلامية التي مارستها هذه القناة فرانس 24 الفرنسية، جاءت هذه الدراسة المختارة لدراسة موضوع جد هام وشائك يتعلق بأمن واستقرار منطقة المغرب العربي خصوصا وإفريقيا عموما، وبعد ا بشأن شكل ومضمون المعالجة الإعلامية لاستقبال تونس لرئيس جبهة البوليساريو الدراسة التحليلية التي قمنا كمشارك في قمة تيكاد 8 توصلنا إلى تحليل الكمي والكيفي لفئات الشكل الذي تضمن تقطيع الحصة حسب الزمن ا تتوافق مع العمل الإعلامي . 􀁹 والمادة المستعملة ليتم التطرق إليها وهي الحديث الصحفي بنسبة كبيرة كو أما التحليل الكمي والكيفي لفئات الموضوع التي ركزت على عدة مؤشرات نلخصها في مايلي: ا تدفع تونس 􀁹 فئة الأزمة بين تونس والمغرب تبدو ان الجزائر هي المتهم الأول في خلق الأزمة وخاصة من المغرب كو لاتخاذ هكذا موقف، ثم فئة اعتراف تونس الضمني بالجمهورية الصحراوية والتي بينتها مؤشرات عدة كاستقبال تونس لرئيس الصحراوي والحلف السياسي بين تونس والمغرب، أما فئة دعم الجزائر للقضية الصحراوية فالجزائر على خلاف سياسي واضح بينها وبين المملكة المغربية كون قضية الصحراء الغربية من أولى أولويات الجزائر على مستوى سياستها الخارجية وتدعم الشعب الصحراوي في تقرير مصيره، وفيما يخص فئة الأهداف فسعت البرامج إلى توضيح م وقف تونس وان لا يفهم موقفها موقف عدائيا وحيادا عن حيادها الايجابي والاتحاد المغاربي مطلب استراتيجي، تليها فئة الاتجاه من استقبال تونس لزعيم جبهة البوليساريو يبدو التأييد غالب على الاعتراض وهذا مؤشر على ان تونس لم تقم إلا بالواجب، بالنسبة للجمهور المستهدف كانت وبشدة عند الجمهور العام نظرا لكون القضية عامة وتخص ا المستضيفة لقمة جميع أطراف عدة، وأخيرا وحدة الفاعل والتي شملت الأطراف الفاعلة في القضية مثل تونس كو ان تونس لها. تيكاد 8 والمغرب المنزعج من استقبال تونس لزعيم البوليساريو والجزائر المتهم الأول في ار Study summary: This study dealt with the issue of the media treatment of the repercussions of the presence of the Sahrawi president at the TICAD summit on Tunisian-Moroccan relations, given the important role played by television programs in the media treatment of political issues. 24 French, this study came with the aim of revealing the nature of the media treatment practiced by this selected channel to study a very important and thorny issue related to the security and stability of the Maghreb region in particular and Africa in general, and after the analytical study that we carried out regarding the form and content of the media treatment of Tunisia’s reception of the head of the Polisario Front as a participant in TICAD 8 Summit We reached a quantitative and qualitative analysis of the categories of the format, which included cutting the share according to time and the material used to be addressed, which is the press talk in a large proportion, as it is compatible with the media work. As for the quantitative and qualitative analysis of the subject categories, it focused on several indicators, which we can summarize as follows: The category of the crisis between Tunisia and Morocco seems that Algeria is the first accused of creating the crisis, especially from Morocco, as it pushes Tunisia to take such a position, then the category of Tunisia's implicit recognition of the Sahrawi Republic, which was shown by several indicators such as Tunisia's reception of the Sahrawi president and the political alliance between Tunisia and Morocco, as for the category of Algeria's support for the cause Saharawi Algeria has a clear political dispute between it and the Kingdom of Morocco, since the issue of Western Sahara is one of the first priorities of Algeria at the level of its foreign policy and supports the Sahrawi people in determining their own destiny. With regard to the category of goals, the programs sought to clarify Tunisia's position and not to understand its position as hostile and neutral from its positive neutrality and union The Maghreb is a strategic demand, followed by the category of direction from Tunisia’s reception of the leader of the Polisario Front, support seems to prevail over objection, and this is an indication that Tunisia has done nothing but duty, with regard to the target audience, it was strongly with the general public due to the fact that the issue is general and concerns all several parties, and finally the unity of the actor, which included The active parties in the case, such as Tunisia, being the host of the TICAD 8 summit, Morocco, which is disturbed by Tunisia's reception of the leader of the Polisario, and Algeria, the prime suspect in Tunisia's dependence on it.
دراسة تحليلية لعينة من برامج فرانس 24الفرنسية